World informatization in conditions of international globalization: Factors of influence - V. Babenko; I. Perevozova; O. Mandych; T. Kvyatko; O. Maliy; I. Mykolenko (Global Journal of Environmental Science and Management)
The level of information today is decisive in the socio-economic development of the country. The purpose of the article is to identify the most influential factors in the process of developing informatization in the context of international globalization. The assessment of factors influencing world information is based on the following stages: forming incoming information about the state of world information, a methodical approach to assessing the impact of world information, modeling the interrelation of components, the influence of world information as hidden factors in the development of information. Factor and correlation analyses are carried out within each cluster with a single level of information by groups of countries. Based on the calculation of factor loads, the most influential indicators have been determined, which serve as the basis for the formation of the informatization process mechanism in the countries of each cluster group. Accordingly, for example, from Innovations and Improvement Factors the major ones were only for the second cluster: Government efficiency and Efficiency of goods market and for the third cluster was the Global Competitiveness Index. The study allowed to determine the main priorities for the development of information in the context of clusters, formed in accordance with the level of information development in the country of each group. Interpretation of the results allowed determining the most influential factors in the development of informatization of the countries of each group, which is the basis for forming recommendations on organizational measures to increase the level of informatization in the context of international globalization.